ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN EFISIENSI OPERASIONAL PADA BANK MANDIRI TASPEN KCP UJUNG BERUNG - Yunika Amelia; Gina Sakinah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the strategic role of accounting information systems (AIS) in improving Bank Mandiri Taspen's operational efficiency, focusing on publicly available data. Using literature review and secondary data analysis, this study analyzes the contribution of AIS to bank performance. The results indicate that AIS implementation, particularly with the New Core Banking System (NCBS) and supporting applications such as ANDAL (General Accounting Report), significantly contributes to operational efficiency. This finding is supported by the trend of an improving Operating Expenses to Operating Income (BOPO) ratio in the bank's financial statements. AIS facilitates business process automation, strengthens internal controls, and provides real-time information critical for decision-making. Overall, this study concludes that AIS is not simply a recording tool, but a key driver of efficiency and a foundation for sustainable growth at Bank Mandiri Taspen.